IMPLEMENTASI STRATEGI PEMASARAN UNTUK MENINGKATKAN VOLUME PENJUALAN PADA CV. MAKMUR BAROKAH (GAFAR AHMAD) DI PASAR RAU KOTA SERANG BANTEN - Suhandi Suhandi (LP2M Universitas Bina Bangsa, 2023)
CV. Makmur Barokah is a family company (Toko Gafar Ahmad), which is engaged in selling clothing products such as: men's sarongs, women's sarongs, koko clothes, batik clothes, batik clothes, prayer equipment, Jln.Samaun Bakrie No.28, Pasar Rau Tanggul area Serang District, Serang City, Banten. The purpose of this research is to analyze the implementation of the marketing strategy applied by CV. Makmur Barokah. The results of this study show that CV. Makmur Barokah has not implemented a marketing mix marketing strategy (product, price, promotion and place), has not implemented an online marketing strategy by implementing e-commerce information technology, lack of quality human resources, so that it affects sales volume